Relevansi Konsep Pemikirain Al-Ghozali Dalam Pendidikan Moral Anak di Era Digital - Hairani, Esi (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
Children's moral education is becoming increasingly important in today's digital age, where technology is increasingly influencing children's daily lives. Children interact with digital technology even from waking up to going back to sleep every day with various platforms or sites they access, which noticeably affects their morality. For this reason, a concept of moral education is needed for children in this digital era. The concept of moral thought from Al-Ghazali, a well-known Muslim philosopher, has relevance in the moral education of children in the digital age. In this article, discusses the implementation of Al-Ghazali's concept of moral thought in children's moral education in the digital age. The method used is a literature study by conducting a literature review and analysis of Al-Ghazali's moral thinking concept and its challenges and solutions in implementing the concept in the digital era. The results of this research show that Al-Ghazali's concept of thinking includes recognizing and understanding good ethical and moral values, instilling a sense of responsibility and accountability in children, teaching children to develop positive traits, building children's understanding of the afterlife and the true purpose of life, as well as instilling an attitude of tolerance and respect for differences between individuals. Although Al-Ghazali's concept of moral thinking is very relevant to apply in children's moral education in the digital age, but there are challenges such as the tendency of children who tend to rely on technology, the lack of time spent with family, and easy access to negative content on the internet. The solution includes introducing Al-Ghazali's moral values early to children, monitoring and regulating children's use of technology, and inviting children to do positive activities and build character. It is hoped that this article can provide insights and solutions for parents and educators in educating children in an increasingly complex digital era.